Current Clinical Applications of Extracorporeal Photochemotherapy. Issue 2 (3rd November 2014) - Capuano, Maria; Sommese, Linda; Pignalosa, Orlando; Parente, Delia; Fabbricini, Rossella; Nicoletti, Giovanni Francesco; De Pascale, Maria Rosaria; Schiano, Concetta; Napoli, Claudio
Abstract From the 1980s, extracorporeal photochemotherapy (ECP) has been shown to be effective in a variety of pathological conditions such as erythrodermic cutaneous T‐cell lymphoma, autoimmune diseases, solid organ allograft rejection and graft versus host disease. To date, ECP represents a non‐aggressive immune modulatory therapy with a low spectrum of toxicity. ECP reduces the alloreactivity promoting the immune tolerance to self. At the same time, it allows the maintenance of immune response integrity of both naive and memory T‐cells. However, the molecular mechanisms of action by which ECP exerts its therapeutic activity are still under investigation. Here, we review molecular mechanisms and clinical applications involved in ECP. The outcome of ECP is difficult due to the lack of reliable predictor factors for the selection of patients and their adequate follow‐up. Since the study of such predictors is important, we also describe some biological markers that enable us to investigate the clinical management of the patients considered for the use of ECP.